Методика технико-экономической оценки эффективности повышения надежности авиационных газотурбинных двигателей военного назначения при их послепродажном обслуживании по нормируемым показателям конечного результата - Asadullin, Marsel' Raufovich (Вестник Пермского университета. Серия «Экономика» = Perm University Herald. ECONOMY; Том 3 № 30 (2016)DO - 10.17072/1994–9960–2016–3–92–104, 2019)
Дается описание конфликта интересов государственного заказчика и головного исполнителя в вопросе повышения надежности авиационной техники в процессе ее послепродажного обслуживания. Показано, что конфликт интересов возникает при традиционном подходе к оплате услуг головного исполнителя по методу «издержки+». В качестве механизма разрешения конфликта интересов приводятся успешно применяемые за рубежом контрактные модели государственно-частного партнерства со схемой оплаты услуг исполнителя по нормируемым показателям конечного результата послепродажного обслуживания авиационной техники. Длительный срок таких контрактов и независимость размера сервисных платежей от фактических затрат исполнителя стимулируют частного партнера к проведению мероприятий, направленных на повышение надежности техники. Показана актуальность проведения технико-экономической оценки эффективности таких мероприятий. Приводятся основные положения методики технико-экономической оценки эффективности повышения надежности авиационной техники на примере парка двигателей, эксплуатируемых в составе расчетной группы военно-транспортных самолетов, при их послепродажном обслуживании по нормируемым показателям конечного результата. В основе методики лежит имитационная модель эксплуатации парка двигателей, позволяющая определять показатели технико-экономической оценки: средняя за период действия контракта исправность расчетной группы военно-транспортных самолетов, эксплуатационные затраты государственного заказчика и прибыль головного исполнителя. На основании разработанной методики экспериментально показано, что при послепродажном обслуживании парка двигателей по нормируемым показателям конечного результата у головного исполнителя существует экономическая заинтересованность в повышении надежности двигателей сверх заданных в нормативной документации требований. Ключевые слова технико-экономическая оценка, имитационное моделирование, исправность авиационной техники, конфликт интересов, послепродажное обслуживание, показатели конечного результата, авиационный газотурбинный двигатель, надежность авиационного двигателя, наработка на досрочный съем двигателя, военно-транспортный самолет. Список литературы References 1. Akims V.M. Bases of reliability of gas-turbine engines: the textbook for students of machine-building specialties of higher education institutions. Moscow, Mechanical engineering Publ., 1981. 207 p. 2. Akims V.M, Starik D.E., Morozov A.A. Economic efficiency of increase in a resource and reliability of gas-turbine engines. Moscow, Mechanical engineering Publ., 1972. 172 p. (in Russian). 3. Aleksandrovskaya L.N., Afana-syev A.P., Lisov A.A. Modern methods of ensuring non-failure operation of difficult systems. Moscow, Logos Publ., 2001. 208 p. (in Russian). 4. Asadullin M.R. The technique of definition of optimum terms of the contract of life cycle (on the example of aviation engine-building).What economic model is necessary to Russia? Materials II of the Perm congress of scientists-economists, 11 February, 2016. Perm, PSU Publ., 2016, pp.126–132. (in Russian). 5. Barzilovich Yu.E., Mezentsev V.G., Savenkov M.V. Reliability of aviation systems. Moscow, Transport Publ., 1982. 182 p. (in Russian). 6. Beshelev S.D., Gurvich F.G. Mathematico-statistical methods of expert estimates. Moscow, Statistics Publ., 1980. 264 p. (in Russian). 7. Questions of the mathematical theory of reliability under the editorship of B.V. Gnedenko. Moscow, Radio and communication Publ., 1983. 376 p. (in Russian). 8. Scraps V.V. Organizational and economic bases of ensuring competitiveness of hi-tech productions (on the example of aviation engine-building): thesis of the Doctor of Economics: 05.02.22. Moscow, 2007. 319 p. (in Russian). 9. Mikhaylov A.A. Model of operation of the park of engines taking into account use of strategy of resource management. The All-Russian scientific and technical conference "The scientific readings on aircraft devoted to N. E. memory of Zhukovsky". The collection of theses. Moscow, VVIA of the prof. N. E. of Zhukovsky Publ., 2004. (in Russian). 10. Lifelong contract. Bulletin of operational information "Moscow Auction", 2014, no.11. Available at: http://e-torgi.ru/index.php/st ati-2/7691-pozhiznennyj-kontrakt (accessed 03.03.2015). (in Russian). 11. Pisarev V.N. Application of the theory of mass service in problems of engineering and aviation providing. Moscow, VVIA of N.E. of Zhukovsky Publ., 1965. 44 p. (in Russian). 12. Rumyantsev E.A., Osovsky V.P., Protopopov V.A. Engineering and aviation ensuring fighting of parts of aircraft of armed forces and operation of the aviation equipment. Moscow, VVIA of N. E. of Zhukovsky Publ., 1989. 398 p. (in Russian). 13. Smirnov N.N. Scientific bases of creation of system of maintenance and repair of the GA planes. Moscow, MGTUGA Publ., 1994. 107 p. (in Russian). 14. Smirnov N.N., Itskovich A.A. Service and repair of the aircraft equipment on a state. 2nd edition added and processed. Moscow, Transport Publ., 1987. 272 p. (in Russian). 15. Chudayeva A.A. Reliability and service life of the equipment as economic category. Messenger of regional public institution, 2009, Issue 8 (102), pp. 150155. (in Russian). 16. Aguilar M., Estrada G., Myers J. Decision-support quantitative models for valuing incentives in performance-based contracts. Monterey, CA, Naval Postgraduate School Publ., 2005. 112 p. (in Russian). 17. Deloitte Consulting LLP. Performance based logistics in aerospace & defense. A rapidly growing market providing lower overall sustainment costs for military equipment and profitable growth opportunities for defense contractors. Available at: http://www.deloitte.com.br/publicacoes/2007/Performance_Based_Logistics_in_A&D.pdf (accessed 29.12.2014). (in Russian). 18. Guajardo J., Cohen A., Kim S., Netessine S. Impact of performance-based contracting on product reliability: an empirical analysis. Available at: http://faculty.som. yale.edu/sangkim/PBC-Reliability-Empirical.pdf (accessed 03.03.2015). 19. Kim S., Cohen M, Netessine S. Reliability or inventory? Analysis of product support contracts in the defense industry. Available at: http://sites.insead.edu/facultyres earch/research/doc.cfm?did=47947 (accessed 14.11.2015). 20. PBC Discussion Paper Vol 1.0. Next generation performance-based support contracts – Achieving the Outcomes that Defence Requires. Available at: http://www.defence.gov.au/dmo/ Multimedia/Next_GPBSC-9-5978.pdf (accessed 15.03.2015). 21. Randall W., Nowicki D., Hawkins T. Explaining the effectiveness of performance-based logistics: a quantitative examination. The International Journal of Logistics Management, 2011, vol. 22, issue 3, pp. 324–348. doi: http://dx.doi.org/10.1108/09574091111181354. 22. Sopranos K. Performance-based logistics helps Boeing boost mission readiness. Available at: http://www.boeing.com/news/fr ontiers/archive/2007/august/i_ids01.pdf (accessed 30.03.2015).